2011
DOI: 10.1371/journal.pone.0026589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fish Oil on the Depletion of Carcinogenic PAH-DNA Adduct Levels in the Liver of B6C3F1 Mouse

Abstract: Many carcinogenic polycyclic aromatic hydrocarbons (PAHs) and their metabolites can bind covalently to DNA. Carcinogen-DNA adducts may lead to mutations in critical genes, eventually leading to cancer. In this study we report that fish oil (FO) blocks the formation of DNA adducts by detoxification of PAHs. B6C3F1 male mice were fed a FO or corn oil (CO) diet for 30 days. The animals were then treated with seven carcinogenic PAHs including benzo(a)pyrene (BaP) with one of two doses via a single intraperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…This gene is inducible by both TZDs [73], and PUFA [74], acts both as epoxygenase and hydroxylase, while producing PUFA-derived lipid mediators, with EPA-derived lipid mediators exerting presumably anti-inflammatory effects [53].…”
Section: Discussionmentioning
confidence: 99%
“…This gene is inducible by both TZDs [73], and PUFA [74], acts both as epoxygenase and hydroxylase, while producing PUFA-derived lipid mediators, with EPA-derived lipid mediators exerting presumably anti-inflammatory effects [53].…”
Section: Discussionmentioning
confidence: 99%
“…The radioactively labeled adducts were separated by multidirectional anion-exchange thin-layer chromatography (TLC) on polyethyleneimine-cellulose sheets and chromatographed overnight (~15 hr) in the first direction (D1) with 2.3 M sodium phosphate, pH 5.75, to purify bulky adducts. The bulky labeled DNA adducts retained in the D1 chromatogram were contact-transferred to fresh thin-layer sheets and adducts were separated two-dimensionally with 3.82 M lithium formate, 6.75 M urea, pH 3.35, and 0.72 M sodium phosphate, 0.40 M Tris, 7.65 M urea, pH 8.20, for the first and second dimensions, respectively (Zhou et al, 2011). Radioactive spots were located by imaging using an Instant Imager from Packard Instrument Co. (800 Research Parkway, Meriden, CT 06450) and by screen-enhanced autoradiography on Kodak XAR-5 X-ray film at -80°C for 22 h. The adducts were expressed as 1 in 10 9 relative adduct labeling (RAL) values, as reported previously (Reddy and Randerath, 1986; Zhou et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al (2013) showed that diet containing Omega-3 can attenuate Hepatic damage caused by ischemia and tissue Reperfusion via reduction of NF-Kb activity 24 .At the same time, Popescu et al (2013) indicated that Omega-3 fatty acid along with diet containing natural calorie and diet with natural lipid has protective effects on nonalcoholic fatty liver disease 25 .Other studies have shown that fish oil diet prevents hepatocyte cancer in B6C3F1 mice 26 .Similarly, Omega-3-rich fish oil improves liver damage caused by LPS through the inhibition of TLR4 signaling pathway and NOD 27 .…”
Section: Resultsmentioning
confidence: 99%